2011
DOI: 10.1149/1.3567593
|View full text |Cite
|
Sign up to set email alerts
|

248nm Process Is Capable for sub 0.09 um Groundrules

Abstract: While the mainstream wafer production is at 0.065 and 0.045 um with 300 mm diameter wafers with ArF exposure tools systems, an idea to explore production feasibility under groundrules smaller than 0.09 um while maintain the cost advantages in KrF exposure tools systems becomes more and more popular and important to all companies including 300mm/200mm FAB. But the k1 factor for sub 0.09um with current popular KrF exposure tools will be about 0.31, which has the same level of complexity in optical proximity cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Based on those techniques some good results have been achieved with KrF exposure tools systems [2][3]. We also demonstrated in our study results for line/space patterns [4][5][6][7].…”
Section: Introductionsupporting
confidence: 69%
“…Based on those techniques some good results have been achieved with KrF exposure tools systems [2][3]. We also demonstrated in our study results for line/space patterns [4][5][6][7].…”
Section: Introductionsupporting
confidence: 69%
“…In previous study, we had demonstrated acceptable process window, DOF, MEEF and LWR. In this paper we will focus on the CD and DOF change with different layout design [13].…”
Section: Methodsmentioning
confidence: 99%
“…When we can not get enough improvement from optics, we still can get it from other parts such as photoresists. Based on this idea, we had proposed some new approaches and achieve positive results [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we need to achieve competitive manufacturing cost by using pure KrF process. It has been studied that KrF process can meet the design requirement at 90 or sub90nm nodes [4][5][6][7][8][9]. If we can deal with smaller EW pattern fidelity and high Ge concentration SiGe film, we can avoid use ArF process and maintain an attractive cost.…”
Section: Lithography Requirement Discussmentioning
confidence: 99%